Development and Validation of Spectrophotometric Method for Simultaneous Determination of Isopropamide and Trifluoperazine in Tablet Dosage Form (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The aim of this study is to develop simple, sensitive, rapid, accurate, precise and economical spectrophotometric method based on simultaneous equation method for the simultaneous estimation of isopropamide and trifluoperazine in combined tablet dosage form. Materials and Methods: The method is based on the simultaneous equation and first-order derivative method for analysis of both the drugs using methanol:water in the ratio of 7:3 (v/v) as solvent. Isopropamide has absorbance maxima at 248.5 nm and trifluoperazine has absorbance maxima at 227.0 nm in methanol. Results and Discussion: The linearity was obtained in the concentration range of 5-30 Î¼g/mL for isopropamide and 2-12 Î¼g/mL for trifluoperazine in both the methods. The concentration of drugs was determined by using simultaneous equation method. The result of analysis has been validated statistically and by recovery studies. The results of mean recovery and other validation parameters were found within the acceptable limits. Both methods were applied to estimate the marketed formulation and found good recovery of the drug. The methods were found to be simple, sensitive, accurate and precise and were applicable for simultaneous determination of isopropamide and trifluoperazine in pharmaceutical dosage form.